A remark on Gwinner's existence theorem on variational inequality problem - V. Vetrivel; S. Nanda (International Journal of Mathematics and Mathematical Sciences)
Gwinner (1981) proved an existence theorem for a variational inequality problem involving an upper semicontinuous multifunction with compact convex values. The aim of this paper is to solve this problem for a multifunction with open inverse values.